2012
DOI: 10.1111/j.1432-2277.2012.01467.x
|View full text |Cite
|
Sign up to set email alerts
|

No ocular involvement in familial amyloidotic polyneuropathy ATTR V30M domino liver recipients

Abstract: Summary In many transplantation centers domino liver transplantation is an established procedure, increasing the number of available liver grafts. Increasingly, grafts from familial amyloidotic polyneuropathy (FAP) patients are used. Ocular involvement is a well known manifestation of FAP, and can be vision‐threatening. The aim of this study was to evaluate the risk of development of familial amyloidotic polyneuropathy ocular manifestations in domino liver recipients. Forty‐four cirrhotic patients submitted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 38 publications
0
12
0
1
Order By: Relevance
“…TTR is also present in the cerebrospinal fluid and aqueous humour [ 5 ]. About 90% [ 11 , 14 ] is synthesised and secreted by the liver and a small portion (<2%) may be synthesised by the brain's choroid plexus, the retinal pigment epithelium (RPE) [ 6 , 11 ], and the small intestine [ 15 ].…”
Section: Structure and Function Of Ttrmentioning
confidence: 99%
See 2 more Smart Citations
“…TTR is also present in the cerebrospinal fluid and aqueous humour [ 5 ]. About 90% [ 11 , 14 ] is synthesised and secreted by the liver and a small portion (<2%) may be synthesised by the brain's choroid plexus, the retinal pigment epithelium (RPE) [ 6 , 11 ], and the small intestine [ 15 ].…”
Section: Structure and Function Of Ttrmentioning
confidence: 99%
“…It has been suggested that plasma TTR does not cross the blood-retinal barrier [ 14 ], despite evidence of progression of ocular manifestations, after liver transplantation. This reaffirms the belief that intraocular amyloid fibrils are not synthesised by the liver but locally at the RPE [ 11 ].…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Orthostatic hypotension (Benson & Kincaid, 2007; Planté-Bordeneuve & Said, 2011; Ando et al , 2013), Nephropathy (Lobato et al , 2003; Benson & Kincaid, 2007; Lobato & Rocha, 2012; Planté-Bordeneuve & Said, 2011; Ando et al. , 2013), Ocular diseases (Benson & Kincaid, 2007; Cunha-Vaz, 2009; Beirão et al , 2012, 2013; Planté-Bordeneuve & Said, 2011; Ando et al. , 2013), Heart diseases (Benson & Kincaid, 2007; Planté-Bordeneuve & Said, 2011; Ando et al , 2013), and reproductive problems.…”
Section: Introductionmentioning
confidence: 99%
“…These include organ transplantation (Furtado, 2000; Sousa et al. , 2004; Benson & Kincaid, 2007; Hou et al , 2007; Lobato & Rocha, 2012; Beirão et al , 2012, 2013; Ando et al , 2013; Castaño et al , 2015), stabilizer agents (Tafamidis: prevent TTR from dissociating into monomers) (Coelho et al , 2012, 2013), gene therapy using antisense oligonucleotides (ASO: cause nuclear degradation of the mutated mRNA (Castaño et al. , 2015; Niemietz et al , 2015), gene therapy using small interference RNA (siRNA: block translation of the mutated mRNA) (Coelho et al , 2013; Castaño et al , 2015; Niemietz et al.…”
Section: Introductionmentioning
confidence: 99%